(untitled) (Anclajes, 2018)
In the framework of a broader investigation into the imaginaries of the afterworld in present-day Argentine literature, this paper aims at addressing the ways in which Carlos Ríos’s Cuaderno de Pripyat (2012) narrates the afterworld of an identifiable historical event, the Chernobyl disaster, creating further tension between the crisis itself and the possibility of a post-apocalyptic setting that brings a radical and immeasurable interruption into play. First, we analyze the ways in which this multiplication of temporalities affects the presentation of the testimonies collected in the story. Next, the paper focuses on the collage as a possible explicative key to the fragmentary composition of the story based on the tension between the rationality of that which remains and that of referential oversaturation.